Analisis faktor-faktor yang mendasari terjadinya manajemen laba - Istiqomah, Putri; Nuswandari, Cahyani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this research is to examine the underlying factors that contribute to the practice of earnings management. The present study employs earnings management as the dependent variable, while incorporating company size, managerial ownership, institutional ownership, profitability, and leverage as independent variables. The present research employs secondary data, specifically financial and annual reports of manufacturing firms that are publicly listed on the IDX, covering the timeframe of 2017-2020. The study employed a purposive sampling technique that involved the application of multiple criteria to select a sample of 199 participants. The employed methodology entails the utilization of multiple linear regression analysis. The findings indicate that earnings management is positively associated with profitability and leverage, while negatively associated with company size. The study found that institutional ownership and managerial ownership do not exert any significant impact on the practice of earnings management.